2003
DOI: 10.1128/cdli.10.3.417-422.2003
|View full text |Cite
|
Sign up to set email alerts
|

Role of Macrophage Migration Inhibitory Factor in Otitis Media with Effusion in Adults

Abstract: Otitis media with effusion (OME) is one of the most common ear diseases. Bacterial endotoxins and several inflammatory cytokines appear to be involved in the pathogenesis of OME in children; however, little is known of the immunological aspects of the onset of OME in adults. We sought to determine the presence of macrophage migration inhibitory factor (MIF) as well as interleukin 1␤ (IL-1␤), tumor necrosis factor alpha (TNF-␣), RANTES (regulated upon activation, normal T-cell expressed and presumably secreted)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
1
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 31 publications
0
16
1
1
Order By: Relevance
“…In this study, we found that the mRNA and protein levels of MIF were up-regulated in mouse AOM model, which was also observed in the pathogenesis of OM [6,10]. ISO-1 is the most frequently studied MIF small molecule antagonist.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…In this study, we found that the mRNA and protein levels of MIF were up-regulated in mouse AOM model, which was also observed in the pathogenesis of OM [6,10]. ISO-1 is the most frequently studied MIF small molecule antagonist.…”
Section: Discussionmentioning
confidence: 90%
“…MIF was originally reported as a cytokine preventing random macrophage migration in tissue with inflammation; however, it has now been reported that MIF has multiple functions, both within and outside of immune system, on pituitary hormone, growth factor, and pro-inflammatory cytokines [5]. Lipopolysaccharides (LPS) from gram-negative bacteria have been shown to be powerful inducers of MIF secretion by macrophages, and autocrine and paracrine signaling of MIF induces the release of tumor necrosis factor (TNF)-α from macrophages in otitis media with effusion (OME) in adults [6]. It has been shown that TNF-αcan modulate the expression of Toll-like receptors (TLR) and is also essential for TLR signaling, including nuclear factor (NF)-κB, via both positive [7] and negative [8] feedback mechanisms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pathogenesis of mucoid OME has been considered to differ from that of serous OME (3). A small number of reports described the cytokine expression in mucoid MEEs of children with OME (17), whereas only one report described the cytokines in mucoid MEEs of adults with OME (6).…”
mentioning
confidence: 97%
“…In addition, allergic mediators, including Th2 cytokines, are considered principally involved in the pathogenesis of OME (3). The lipopolysaccharides present in high percentage in middle ear effusions (MEEs) of adults with OME (6), and IL-12 promotes the secretion of IFN-F, IL-2, IL-8, and granulocytemacrophage colonyYstimulating factor under the stimulation of lipopolysaccharides (7,8).…”
mentioning
confidence: 99%